PENGARUH KONDISI LINGKUNGAN TERHADAP SERANGAN PENGGEREK KAYU DI LAUT - Mohammad Muslich; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
One hundred and twenty five pieces of wood from five species had been exposed to Marine Borers in five different locations. The test sites chosen were around Gulf of Jakarta, i.e. about 3 km off shore in Mauk, Mauk estuary, Tanjung Pasir shore, Rambut Island and Puntung Java Island.The result shows that at the sea site where the salinity is relatively stable around 29‰ - 30‰ and at the Rambut and Puntung Java Islands 30‰ - 34‰, all of the wood tested are badly attacked by Marine Borers. The result also shows that at the Mauk estuary and Tanjung Pasir shore where the salinity 5°/oo - 30°/oo, damage is only small